The Intersection of Faith and Pornography: A Turkish Moral Disapproval of Pornography Scale - EKŞİ, HALİL (My University, 2024)
The development process and validity and reliability studies of the \"Moral Disapproval of Pornography Scale\" (MDSS) are described in this study. Moral disapproval of pornography use, one of the three components of the Anti-Pornography Problems Associated with Moral Inconsistency (APPM) model, refers to the psychological difficulties created by individuals’ pornography use that contradicts their moral beliefs about pornography. This incongruence is shown to have a moderating role between individual’s self-perception of addiction and their psychological well-being. In studies conducted abroad, it is seen that the phenomenon in question is examined with instruments consisting of moral and religious oriented items. These items were culturally adapted and turned into a scale that people with different religious beliefs and practices can easily answer. The exploratory factor analysis of the obtained scale was conducted with 634 participants. Subsequently, a confirmatory factor analysis of the scale was performed with a second sample of 580 individuals. The Cronbach’s alpha coefficient for internal consistency was calculated as .862, and McDonald’s Omega coefficient of .85, indicating good reliability. The exploratory factor analysis revealed that 71% of the total variance was explained and the items were loaded onto a single factor. In the confirmatory factor analysis, acceptable fit indices [χ2 / df = 1.81, RMSEA = .005, AGFI = 0.97, CFI = 0.99, GFI = 0.98, RMR = 0.02] were obtained. Any criterion scale for moral disapproval of Pornography was not used to determine the concurrent validity due to lacking a previously developed scale in Turkish. In conclusion, the Pornography Moral Disapproval Scale (PMDS) was found to be a valid and reliable measure.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Social Sciences and Humanities; Psychology; Temel Bilimler (SCI); Natural Sciences (SCI); PSYCHOLOGY; Psikoloji (çeşitli); Sosyal Bilimler ve Beşeri Bilimler; Psychology (miscellaneous); Social Sciences & Humanities; Moral disapproval; Moral incongruence; Pornography use; Religiousness